(untitled) (Journal of actual problems of jurisprudence, 2019)
As a result, the number of many rare and endangered species of plants and animals living on the territory of the Republic of Kazakhstan, as statistics, has been steadily declining. Environmental Code of the Republic of Kazakhstan in its flora species diversity in all areas of growth is defined as an independent object of legal protection. However, the Forest Code of the Republic of Kazakhstan regulates only certain relationships protection and use of the plant world. And as we noted earlier, the forest is the only part of the plant world. Thus, we can conclude that the national legislation of Kazakhstan settled the issue only in respect of forest vegetation in this regard, there is need for training and the adoption of the Law of the Republic of Kazakhstan "On Flora". Keywords: Rare and endangered species of plants, protection, environment, flora, fauna.